EFL LEARNERS’ AND TEACHERS’ POSITIVE ATTITUDES TOWARDS LOCAL COMMUNITY BASED INSTRUCTION - Kanoksilapatham, Budsaba; Channuan, Paweena (Universitas Pendidikan Indonesia, 2018)
The new status of the English language as an international language (EIL) in the age of globalisation has contributed to a cultural change of focus in English language teaching (ELT). Instead of paying attention to cultural aspects of native English speakers as in traditional English instruction, cultural diversity now plays a key role in the teaching of culture in order to enhance leaners‟ intercultural awareness. To fill this need, this study aims to document EFL learners‟ and teachers‟ attitudes towards local community instruction in which young Thai students learned English whilst being encouraged to take pride in their local culture. In this study, a set of local community-integrated lessons for elementary English education were constructed and subsequently implemented in Grade 4 classes at schools in the northern region of Thailand. Questionnaires were then administered to the students, and semi-structured interviews were also conducted with the school English teachers to elicit their attitudes towards the integrated lessons. The results indicated that young Thai students, along with their English teachers, have highly positive attitudes towards the local community based instruction. This lead to significant implications related to integrating aspects of local cultural identity into ELT practices.